Leverage and internal capital markets: evidence from leveraged recapitalizations - Peyer, U (Journal of Financial Economics, 2001)
We study the internal allocation of resources for diversified firms that complete a leveraged recapitalization. Before the recapitalization, internal capital markets allocate investment to high q segments. After the recapitalization, segment investment becomes less sensitive to q and more sensitive to segment cash flow. We show that firm value is positively related to investment's sensitivity to segment q and negatively related to investment's sensitivity to segment cash flow. Our analysis highlights an indirect cost of debt that has received little attention: pressure to meet interest obligations creates an incentive to emphasize investments that generate high levels of current cash flow.